Evaluación de los parámetros productivos en terneros en la etapa de crecimiento de la raza holstein con dieta a base de aceite de orégano como suplemento en la parroquia Machachi cantón Mejía - Lisintuña Montaguano, Jorge Oswaldo (2014)
This research has done in Machachi, Mejia Canton, Pichincha Province The main goal of the research was point out and evaluates the productive parameters in calf’s based on oregano oil as a profit on a daily diet The test was done with three treatments: The first treatment with seven animals they received 2 ml of oregano oil as a daily profit for 90 days. The second treatment was done with seven animals and they received 1 ml of oregano oil as a daily profit for 90 days. The third treatment was the normal nursing of the animal. The result of the research was that the treatment of the animals on the first treatment had win weight and increased the community that rises the result s of the immunity increase was made through blood exams (Hematic biometry). The following research was positive because of we got a healthy animals without illnesses had they had got weight like 700 grams per day....